Behavorial responses in large carnivores to mammalian blood odor and a blood odor component - Nilsson, Sara; Sjöberg, Johanna; Amundin, Mats; Hartmann, Constanze; Büttner, Andrea; Laska, Matthias (PLoS ONE, 2014)
Only little is known about whether single volatile compounds are as efficient in eliciting behavioral responses in animals as the whole complex mixture of a behaviorally relevant odor. Recent studies analysing the composition of volatiles in mammalian blood, an important prey-associated odor stimulus for predators, found the odorant trans-4,5-epoxy-(E)-2-decenal to evoke a typical “metallic, blood-like” odor quality in humans. We therefore assessed the behavior of captive Asian wild dogs (Cuon alpinus), African wild dogs (Lycaon pictus), South American bush dogs (Speothos venaticus), and Siberian tigers (Panthera tigris altaica) when presented with wooden logs that were impregnated either with mammalian blood or with the blood odor component trans-4,5-epoxy-(E)-2-decenal, and compared it to their behavior towards a fruity odor (iso-pentyl acetate) and a near-odorless solvent (diethyl phthalate) as control. We found that all four species displayed significantly more interactions with the odorized wooden logs such as sniffing, licking, biting, pawing, and toying, when they were impregnated with the two prey-associated odors compared to the two non-prey-associated odors. Most importantly, no significant differences were found in the number of interactions with the wooden logs impregnated with mammalian blood and the blood odor component in any of the four species. Only one of the four species, the South American bush dogs, displayed a significant decrease in the number of interactions with the odorized logs across the five sessions performed per odor stimulus. Taken together, the results demonstrate that a single blood odor component can be as efficient in eliciting behavioral responses in large carnivores as the odor of real blood, suggesting that trans-4,5-epoxy-(E)-2-decenal may be perceived by predators as a “character impact compound” of mammalian blood odor. Further, the results suggest that odorized wooden logs are a suitable manner of environmental enrichment for captive carnivores.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.behavo